A Fundamental Factorization Lemma Revisited (European Journal of Pure and Applied Mathematics, 2026)
Lemma 3 in the paper [1] [Communications in Algebra, 49(6), 2722–2727, 2021] is revisited. In this paper, we provide an improvised rudimentary proof of the same.
Keywords: Irreducibility of Polynomials; Integer coefficients; Irreducibility Criterion.